Graphene nanoribbon-based supramolecular ensembles with dual-receptor targeting function for targeted photothermal tumor therapy. Issue 33 (22nd July 2021) - Dou, Wei-Tao; Xu, Fugui; Xu, Chen-Xi; Gao, Jie; Ru, Hong-Bo; Luan, Xiangfeng; Zhang, Jiacheng; Zhu, Ling; Sedgwick, Adam C.; Chen, Guo-Rong; Zang, Yi; James, Tony D.; et al.
Abstract : Dual receptor-targeting supramolecular glycomaterials are constructed based on graphene nanoribbons for the targeted photothermal therapy of triple-negative breast cancer in vivo . Abstract : Triple negative breast cancer (TNBC) is one of the most malignant subtypes of breast cancer. Here, we report the construction of graphene nanoribbon (GNR)-based supramolecular ensembles with dual-receptor (mannose and αv β3 integrin receptors) targeting function, denoted as GNR-Man/PRGD, for targeted photothermal treatment (PTT) of TNBC. The GNR-Man/PRGD ensembles were constructed through the solution-based self-assembly of mannose-grafted GNRs (GNR-Man ) with a pyrene-tagged αv β3 integrin ligand (PRGD ). Enhanced PTT efficacies were achieved both in vitro and in vivo compared to that of the non-targeting equivalents. Tumor-bearing live mice were administered (tail vein) with GNR-Man/PRGD and then each mice group was subjected to PTT. Remarkably, GNR-Man/PRGD induced complete ablation of the solid tumors, and no tumor regrowth was observed over a period of 15 days. This study demonstrates a new and promising platform for the development of photothermal nanomaterials for targeted tumor therapy.